METHODOLOGY FOR EDUCATING SPIRITUAL AND MORAL VALUES IN THE EDUCATIONAL PROCESS BASED ON AN INTERDISCIPLINARY APPROACH (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article briefly discusses the methodology for educating spiritual and moral values in the educational process based on an interdisciplinary approach.